Study of Vitamin D Deficiency on Pregnancy Women in Rupat Utara District Bengkalis Regency Riau Province (Future Science, 2022)
Vitamin D is a potent steroid hormone calcitriol precursor which is known to have important roles during pregnancy, especially for fetal growth. Previous research proved vitamin D supplementation during pregnancy can decrease the risk for women to give birth to small for gestational age babies. Rupat Utara District is a remote area and located far from secondary health care facilities or hospitals, therefore iexat became one of the most concerning areas in Bengkalis Regency due to the high number of stunting cases. This is why complete examination in pregnant women with vitamin D deficiency risks living in Rupat Regency is important to lower the number of stunting cases. This study is aimed to describe the prevalence and understand the factors that can contribute to vitamin D deficiency conditions in pregnant women. This study used the descriptive method. The sample recruited was pregnant women living in Rupat Utara District and 35 pregnant women matched the inclusive and exclusive criteria for the study. The result showed that the number of vitamin D deficiencies was 60%. Subjects with vitamin D deficiency mostly were in the third semester gestational age (42.9%), Melayu ethnicity (71.4%), not working (81.0%), being outside for less than 1 hour/day (71.4%), and not regularly taking vitamin D supplementation before the study (57.1%). This high number of vitamin D sufficiency in Rupat Utara District reflected how vitamin D supplementation during pregnancy is important.